Penerapan Pendidikan Akhlak Santriwati dalam Kitab Akhlak lil Banat: Studi Pondok Pesantren Salaf Al-Mardliyah Tambak Beras Jombang - Itiqotul; Nadlif, Ainun; Puji Astutik, Anita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Moral education is a very important thing to do, this is based on the phenomenon that occurs in the era of society 5.0 which is very fast in anything. Character education can be said to be successful if it can be applied and carried out in everyday life, this is the result of learning formed slowly through knowledge and then carried out. The character education that will be studied by the researcher is moral education resulting from teaching and examples of a book of morals lil banat which is one of the bases in learning carried out at the Al Mardliyyah Islamic boarding school. This study aims to examine the application of moral education of female students based on the Book of Akhlakul Lil Banat at the Al-Mardliyah Islamic Boarding School, Tambakberas, Jombang. The research method used is the analytical descriptive method with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the implementation of moral education for female students at the Al-Mardliyah Tambakberas Jombang Islamic Boarding School is carried out systematically and in a planned manner through direct teaching from the Akhlakul Lil Banat book delivered by the kyai and ustadzah with various relevant learning methods. The implication of this study is the importance of developing a more integrated and contextual curriculum for female students' moral education in accordance with the development of the times.